PEMBUATAN ZAT WARNA ALAM DARI TUMBUHAN BERASAL DARI DAUN - Adella Hotnyda Siregar (Bina Teknika, 2016)
Plant from the earth can used as dyes for colouring textiles. The leveas must be extracted with boil water until thick with viscouscity. Dyes with viscouscity from plant are non carsinogen. Its used for dyeing textile .